OPTIMALISASI KEUNTUNGAN WARUNG LAMONGAN DENGAN (METODE SIMPLEX PROGRAM LINEAR) RISET OPERASI - Putri Marsya; Husnatun Syahira; Alya Nazwa; Ismar Hidayat (Jurnal Riset Multidisiplin Edukasi, 2026)
Micro, small, and medium-sized enterprises (MSMEs) in the Lamongan culinary sector hold significant economic potential; however, they often face constraints due to sub-optimally managed resources, preventing the realization of maximum profits. This study aims to determine the optimal production mix for four grilled product variants—grilled chicken, duck, catfish, and tilapia—to maximize business profits. A linear programming approach was employed, utilizing the Simplex algorithm for the solution. The objective function was formulated based on daily operational data, including the availability of key ingredients, seasonings, and supporting facilities, as well as work time allocation. The results indicate that the optimal solution is achieved by producing 40 portions of grilled duck and 15 portions of grilled tilapia, while the production of grilled chicken and grilled catfish is not recommended. This production combination yields a maximum net profit of IDR 740,000.00 per day and ensures the most efficient use of key ingredients and seasonings. The method demonstrates the ability to generate solutions that are quantifiable and adaptable to changing operational conditions, thereby serving as a practical decision-support tool for culinary business operators.